PENERAPAN METODE MULTI-OBJECTIVE OPTIMIZATION ON THE BASIS OF RATIO ANALYSIS (MOORA) DALAM SISTEM PENDUKUNG KEPUTUSAN PENENTUAN KADAR MINYAK MENTAH - Rizky Hendro Agung; Budi Serasi Ginting (STMIK KAPUTAMA, 2020)
PT Perkebunan Nusantara IV Jambi Bah Plantation Business Unit is one of the large oil palm plantations that produce crude palm oil.The requirements for the quality of palm oil used as raw material for the food and non-food industries are different. Therefore authenticity, purity, freshness and other aspects must be paid more attention. The selection of crude palm oil levels carried out in the processing section is still manually. This requires quite a long time in the process and does not rule out the possibility of errors in his judgment. Based on the above assessment, there is a problem often found in determining high-quality and high-quality oil, which is to determine the appropriate and appropriate assessment in grading the content or aspects contained in crude oil according to standards and quality. Based on these problems, we need a system that is able to help solve problems in determining the quality of crude oil levels and quality. Thus it can be proposed operational development in determining the levels contained in crude oil using the MOORA method in deciding quality oil levels based on existing criteria. From the test results tested with 16 alternatives, the highest results can be obtained, namely alternative A3 with an alternative name 8774 LU with a value of 0.2738 so that it can be concluded that alternative A3 has high quality and quality oil content.